2020
DOI: 10.3389/fnut.2020.581723
|View full text |Cite
|
Sign up to set email alerts
|

Maternal High-Fat Diet Leads to Non-alcoholic Fatty Liver Disease Through Upregulating Hepatic SCD1 Expression in Neonate Rats

Abstract: Non-alcoholic fatty liver disease (NAFLD) has become the leading cause of liver disease in children, with evidence that the maternal diet and the early life nutritional environment are potential risk for such disease. This study was aimed to investigate the effects of maternal high-fat diet (HFD) on the occurrence of NAFLD in offspring rats and the underlying mechanisms. In this study, the incidence of NAFLD was compared in F1 offspring rats between the maternal HFD group and standard chow (SC) group. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 48 publications
1
13
0
4
Order By: Relevance
“…Although not expressly investigated in these studies, the reported effects may lead to a decrease or increase in nutrient availability, respectively, which may have potential adverse health effects as reported for similar variations in "normal" nutrients (Agarwal et al, 2018;Baker and Friedman, 2018;Cao et al, 2020).…”
Section: Developmental Programming and Possible Complications Of Precocious Maturation Of The Git Through Medicinal Plants And Phytochemimentioning
confidence: 94%
“…Although not expressly investigated in these studies, the reported effects may lead to a decrease or increase in nutrient availability, respectively, which may have potential adverse health effects as reported for similar variations in "normal" nutrients (Agarwal et al, 2018;Baker and Friedman, 2018;Cao et al, 2020).…”
Section: Developmental Programming and Possible Complications Of Precocious Maturation Of The Git Through Medicinal Plants And Phytochemimentioning
confidence: 94%
“…Leptin-deficient ob/ob mice showed lipid accumulation in their livers, and a lack of SCD1 can lead to a significantly decreased body weight ( Cohen, 2002 ). NAFLD in neonate rats could be induced by a maternal high-fat diet through the up-regulation of SCD1 expression ( Cao et al, 2020 ). CRISPR/Cas9-mediated SCD1 deficiency decreased lipid synthesis gene expression and TAG content in goat mammary epithelial cells ( Tian et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Information on childhood factors, including average hours of exercise and sedentary activities (screen time), diet quality score, and calorie intake, was obtained from postnatal questionnaires around the age of 9 years, except for sugar intake and breastfeeding, which were obtained from postnatal questionnaires about the first year of life (18). Covariates were selected if there were strong correlations with high BMI, liver fat accumulation, and risk of NAFLD (2,(5)(6)(7)12,(27)(28)(29)(30).…”
Section: Covariatesmentioning
confidence: 99%
“…Furthermore, previous studies have suggested that maternal factors, pregnancy factors, or lifestyle factors are associated with liver fat (13)(14)(15)(16)(17)27,28,(39)(40)(41). Factors such as education level of the mother, higher prepregnancy BMI, sugar intake in early life, and sedentary lifestyle have all been associated with a higher risk of developing NAFLD in childhood (13,15,28,39,41).…”
Section: Interpretation Of Main Findingsmentioning
confidence: 99%